Prehydrated collagenated cortico‐cancellous heterologous bone gel and papillae tunneling for isolated intrabony defects: 12‐month noninferiority trial - Tom Kobe; Katja Povšič; Rok Gašperšič (Wiley, 2024)
Abstract Objectives This study assessed the effectiveness of prehydrated collagenated xenogenic bone gel and a collagenated cortico‐cancellous heterologous bone mixture in conjunction with papillae tunneling techniques (PTT) for treating isolated periodontal intraosseous defects. Materials and Methods Twenty patients with periodontitis stage III/IV and at least one deep isolated interdental 2/3‐wall intraosseous defect were included in the study. Surgical incisions were made vertically at the adjacent tooth or horizontally at the mucogingival junction. A full‐thickness flap was then carefully lifted under the papillae using special tunneling instruments. The root surfaces were completely cleaned, and the defects were randomly filled with either prehydrated collagenated bone gel (test group; n = 10) or collagenated cortico‐cancellous heterologous bone mixture (control group; n = 10). Wounds were closed with microsurgical sutures. We predicted that the lower 95% confidence interval for the difference between the two procedures would exceed a prespecified noninferiority threshold. Results All wounds closed sufficiently to prevent biomaterial exposure. The test and control groups showed similar mean pocket depth reduction (3.5 ± 1.0 vs. 3.9 ± 1.7 mm; p = 0.52), similar gingival recession (−0.10 ± 0.99 vs. 0.2 ± 0.8 mm; p = 0.46), and similar clinical attachment gain (3.6 ± 1.51 vs. 3.7 ± 1.8 mm; p = 0.89) at the 12‐month follow‐up. All results were below the noninferiority margin of the sample. Conclusions At 12 months, prehydrated collagenous bone gel performed similarly to collagenous heterologous bone granules in the treatment of intraosseous lesions with PTT. In addition, both biomaterials preserved soft tissue with minimal further recession at 1 year. Clinical Relevance When combined with PTT, collagenous xenogeneic bone granules and prehydrated collagenous bone gel achieve comparable clinical outcomes in intrabony defects. The study was registered under the NCT 04782921 on ClinicalTrails.